Regulation of Taxi Markets in Developing Countries : Issues and Options - Gwilliam, Kenneth M. (World Bank, Washington, DC, 2012)
Taxis perform an important function in urban transport markets in both developed and developing countries. Because of the perceived vulnerability of passengers to exploitation by operators, entry to the market and fares have been tightly regulated in many industrialized countries. This has typically produced high premium values for licenses, implying some monopoly profit for operators at the expense of users. Curiously, however, total deregulation has often increased fares. This note considers the reasons for increased fares despite deregulation, the regulatory options available, and the relevant considerations in applying this experience to developing countries.